Ecological Conditions And Economic Values Of Coral Reef Flats In Mattiro Deceng Village, Badi Island, Pangkajenne Kepulauan Regency, South Sulawesi - Ella Maria Tudang; Unstain N. W. J. Rembet; Adnan S Wantasen (Sam Ratulangi University, 2019)
This research was carried out in Badi Island waters on Mattiro Deceng Village, Pangkajenne Kepulauan Regency, South Sulawesi. The aims of this study are to know the ecological conditions of the coral reef ecosystem at; and to calculate the economic value of coral reef ecosystems at the research area. To determine the ecological conditions of coral reefs, data were obtained by using the Transect Line Intercept (LIT) method which were used in 3 different locations including: inner reef, middle reef, and outer reef. All benthic biota passed through the transect were recorded based on their growth form. On the other hand, to obtain the total economic value, interviews were conducted within the community who were active in utilizing the coral reef ecosystem by using the purposive sampling method. The condition of the coral reef of Badi Island on inner reef area (48.62%) was considered in the medium category and for the middle reef area is 64.10% and the outer reef area is 50.01% were both considered in the good category. The total economic value of Badi Island's coral reef ecosystem in Mattiro Deceng Village is Rp. 10,567,286,000 / year, whereas for the direct benefit calculated value is Rp. 9,213,714,286 / year and for the value of indirect benefits is totaling Rp. 1,353,572,000/year.Keywords: Ecological Conditions, Economic Value, Coral ReefsABSTRAKPenelitian ini dilakukan di Perairan Pulau Badi Desa Mattiro Deceng Kabupaten Pangkajenne Kepulauan, Sulawesi Selatan dengan tujuan untuk: 1. Mengetahui kondisi ekologi ekosistem terumbu karang pada lokasi penelitian. 2. Mengetahui nilai ekonomi ekosistem terumbu karang pada lokasi penelitian. Untuk menentukan kondisi ekologi terumbu karang akan di peroleh dengan menggunakan metode Line Intercept Transek (LIT) pada 3 lokasi berbeda yaitu inner reef, middle reef, dan outer reef, dimana setiap biota bentik yang dilewati transek akan dicatat menurut bentuk pertumbuhannya. Sedangkan untuk memperoleh nilai ekonomi total dilakukan wawancara kepada masyarakat yang beraktivitas di ekosistem terumbu karang dengan menggunakan metode Purposive Sampling. Kondisi terumbu karang Pulau Badi pada inner reef (48,62%) termasuk dalam kategori sedang dan pada middle reef ( 64,10%) dan outer reef (50,01%) termasuk dalam kategori baik. Nilai total ekonomi ekosistem terumbu karang Pulau Badi Desa Mattiro Deceng sebesar Rp. 10.567.286.000/tahun, dimana untuk nilai manfaat langsung sebesar Rp. 9.213.714.286/tahun untuk nilai manfaat tidak langsung sebesar Rp. 1.353.572.000/tahun.Kata Kunci : Kondisi Ekologi, Nilai Ekonomi, Terumbu Karang